Development of a gluten-free pasta based on oat flour, quinoa, and cactus cladode pulp: evaluation of cooking parameters, nutritional contribution, bioactive compounds and sensory quality - Jorge Gutiérrez-Tlahque; César U. López-Palestina; Julia M. Alatorre-Cruz; María S. Espinoza-Rodríguez; Susana E. Altamirano-Romo; Thania A. Urrutia-Hernández; Yair O. Santiago-Sáenz (Applied Food Research)
Nowadays, efforts have been made to improve pasta nutritional and functional value based on durum wheat by including non-conventional gluten-free ingredients. For this reason, the research aimed to prepare gluten-free fettuccine-type pasta based on oat flour (O), quinoa (Q), and cactus cladode pulp (CP) and evaluate the cooking properties, nutritional contribution, bioactive compounds, antioxidant activity, and sensory quality of the product. Three formulations were obtained based on the oat-quinoa-cactus pulp (O-Q-CP) mixture in 100 g, which were 50-10-40, 52-8-40, and 54-6-40 corresponding to treatments T1, T2, and T3 respectively, which were compared against a control (C) that consisted of a commercial pasta. The results indicate that T3 pasta increased the ash, protein and fiber content to a 2.15, 1.12 and 3.04 times higher respectively compared to commercial pasta. All the proposed formulations had lower carbohydrate content. However, a higher oats content in the formulation led to T3 pasta being the richest in fat. A greater contribution of bioactive compounds such as total phenols, flavonoids, and chlorophylls was observed in gluten-free pasta, which led to an increase in antioxidant activity up to values of 284.38 µM of Trolox 100 g-1 in T2 pasta, this represented approximately 2.8 fold more than the control pasta. However, they presented lower sensory acceptance and lower quality regarding cooking parameters. Finally, oat flour, quinoa, and cactus cladode pulp are recommended as alternative ingredients rich in bioactive compounds to obtain gluten-free pasta, however, the sensory parameters of taste and texture, specifically, require further investigation.